STRATEGIC VISIONS OF DEVELOPMENT OF THE REGIONAL ECONOMY - Zarichna , O.V. (The actual problems of regional economy development, 2020)
The objective of the article is to study of basic strategic priorities of regional development of the state from taking into account of influence of basic factors and indexes of regional development, and also excretions of basic strategies, that assist the increase of level of regional economy in the conditions of economic instability. The research used methods of systematization, grouping, abstraction to determine the essence of the concept of "regional economy", methods of statistical and strategic analysis to study and assess some indicators of socio-economic potential and strategic vision of the prospects of Ukraine. Database of scientific research was made up of scientific works of domestic scientists-economists and legislatively-normative documents served as on questions state strategic development of regional politics, and also statistical data of government service of statistics of Ukraine. Essence of concept "regional economy" is investigational, basic strategic priorities of change and forming of prospects of development of regional economy are certain for the sake of being of effective methods and receptions of overcoming of "deformations". The results of state strategy of regional development and most essential indexes of socio-economic development of regions of Ukraine are analysed and on the basis of their estimation basic strategic directions of improvement of development of regional economy are distinguished in a prospect. The scientific value of the got results consists in determination and opening of directions of development of regional economy taking into account transformation processes. The got results of research can be drawn on in future at development of Strategy of regional development of regions of Ukraine.